Service Quality Analysis with Service Performance and Importance Performance Analysis in Hospital - Putri, Pramisyela Adinda; Aryanny, Enny (Journal La Medihealtico, 2024)
Hospital X is a private hospital in Surabaya which was inaugurated in 1995. There are many types of medical facilities and services is at Hospital X, one of the outpatient services. In implementation, Hospital X received complaints from visitors as a result the services it provides. This research aims to understand the extent where is the quality of service provided using the Service Performance method and Importance Performance Analysis (IPA) as well as providing suggestions for improvements right. This research begins with data collection and distribution questionnaire, analyzing data using the Service Performance method and for find out the quality of Hospital X's services and provide suggestions for improvement. Based on the results of research on Service Performance, it was found percentage of patient satisfaction level with the quality of hospital services X is 70%, which means that patients are satisfied with the services provided. The prioritized attributes are fast and precise acceptance procedures (X10), service according to SOP (X11), uncomplicated service procedures (X12), fast drug service time (X13), employees and medical personnel are responsive if there are complaints from visitors (patients) (X15), medical personnel try to help the patient solving problems encountered (X16), speed of medical services (X18), accuracy of medical services (X19), and employees are alert in serving prospective patients (X20).